Efeito da adição de grafite expandido por microondas nas propriedades térmicas, elétricas e mecânicas de nanocompósitos de matriz epóxi - Marinho, Antônio Calmon de Araújo (2014)
Epoxy based nanocomposites with 1 wt % and 3 wt % of nanographite were processed by high shear mixing. The nanographite was obtained by chemical (acid intercalation), thermal (microwave expansion) and mechanical (ultrasonic exfoliation) treatments. The mechanical, electrical and thermal behavior of the nanocomposites was determined and evaluated as a function of the percentage of reinforcement. According to the experimental results, the electrical conductivity of epoxy was not altered by the addition of nanographite in the contents evaluated. However, based on the mechanical tests, nanocomposites with addition of 1 wt.% and 3 wt.% of nanographite showed increase in tensile strength of 16,62 % and 3,20 %, respectively, compared to the neat polymer. The smaller increase in mechanical strength of the nanocomposite with 3 wt.% of nanographite was related to the formation of agglomerates. The addition of 1 wt.% and 3 wt.% of nanographite also resulted in a decrease of 6,25 % and 17,60 %, respectively, in the relative density of the material. Thus, the specific strength of the nanocomposites was approximately 33,33 % greater when compared to the neat polymer. The addition of 1 wt.% and 3 wt.% of nanographite in the material increased the mean values of thermal conductivity in 28,33 % and 132,62 %, respectively, combined with a reduction of 26,11 % and 49,80 % in volumetric thermal capacity, respectively. In summary, it has been determined that an addition of nanographite of the order of 1 wt.% and 3 wt.% produced notable elevations in specific strength and thermal conductivity of epoxy